Robotic adrenalectomy: the jury is still out - Ball, Mark W. (Gland Surg, 2015)
A minimally-invasive approach is the gold standard for surgical management of the majority of adrenal masses. While laparoscopy has traditionally been used, robotic adrenalectomy is becoming increasingly utilized. This article discusses a recent systematic review and meta-analysis from European Urology that analyzed evidence comparing laparoscopic and robotic adrenalectomy. Robotic adrenalectomy is associated with lower blood loss, length of stay and fewer complications compared to laparoscopic adrenalectomy; however information on efficacy and cost are not addressed. Ultimately, well-done randomized controlled trials (RCTs) are necessary to determine the benefits and cost of robotics in adrenal surgery.